Improving English Reading Skills through the Audiovisual Text Media - Suparman, Suparman; Sani, Hasrul (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study aims to analyze "Improving English Reading Skills through the Audiovisual Text Media" among first-semester students of the English Language and Culture Study Program at Sumbawa University of Technology. This research is a quantitative study using a pre-experimental design approach (nondesign). The design consists of a one-group pretest-posttest design with a single predetermined group. The research sample comprises 10 students. The research instrument used to collect data is a test, which includes a pretest and a posttest. The results of this study indicate that the use of the Audiovisual Text Media can improve students' reading ability. This is supported by the analysis using the Paired Test, where the t-value is -42.052 with a significance value (2-tailed) of 0.000. Comparing this with the tabulated significance value (0.05), it is evident that there is a difference between the pretest and posttest scores regarding improving English reading skills through the audiovisual text media.